FAKTOR PENDORONG INTERVENSI MILITER ARAB SAUDI DALAM KONFLIK YAMAN - Purwono, Andi; Sholihul, Ahmad (Interdependence Journal of International Studies, 2023)
In 2014, Houthi rebels seized control of the Yemeni capital, Sana'a. This causes instability in Yemen and disrupts Yemen's neighboring countries, one of which is Saudi Arabia. Houthi rebels. The method used in this study is descriptive qualitative, using secondary data as the source and complemented by the theory of national interest put forward by Donald E. Neuchterlein. The data collection technique used is literature study. The results of this study state that the military intervention carried out by the Arabs against Yemen was driven by national interests including defense interests, economic interests, world order interests, and ideological interests.